Propuesta de plan de gestión integral para los residuos sólidos domiciliarios generados en la cabecera cantonal de Macará, provincia de Loja - Paredes Granda, Leinns Yeison (2018)
Abstract:The current work had the objective of elaborating an integral management plan for solid waste generated in the cantonal capital of Macará in the province of Loja, which currently presents some problems derived from the lack of segregation and use of waste, which has a direct impact on the quality of life of the population and on the environment. First, an evaluation of the current waste management system was carried out through citizen surveys, interviews with the competent authorities and observation visits in the city, and a sampling programmes was developed through which the generation rate was determined to be 0,57 kg / inhab / day per capita of the place, where 81% corresponds to organic waste, 14% to inorganic waste and 5% to lavatory waste. Finally, the proposal for a comprehensive solid waste management plan was designed, consisting of three programmes: Environmental Education, Solid Waste Use, Segregation and Solid Waste Storage; which establish the necessary activities and strategies for their successful implementation.